Counterrevolution, the Spectacle, and the Situationist Avant-Garde - Rasmussen, Mikkel Bolt (Social justice, 2006)
Part of a special issue on art, power, and social change. Of the artistic movements that emerged after World War II, it is the Situationist International that stands out with its persistent, grandiloquent claim to transcend art in a revolutionary act. The Situationists rejected the art institution with militant fervor, contending that the isolated work of art no longer possessed critical potential and that art had to die. Indeed, after a few years they excluded almost all practicing artists from the group in the hope of releasing a post-artistic revolutionary praxis from the confines of the formal art world. The writer examines the Situationist view of the avant-garde, using Guy Debord's 1957 text “Rapport sur la construction des situations et sur les conditions de l'organisation et de l'action de la tendance situationniste internationale” as his starting point.